Shear wave elastography in optic neuritis: diagnostic accuracy of the optic nerve and adjacent fat tissue values - Aybar Mustafa Devran; Turna Onder (Journal of Ultrasonography, 2021)
Introduction: In this study, we attempt to determine the diagnostic performance of shear wave elastography of the optic nerve and adjacent fat tissue in patients with optic neuritis. Methods: The study included a patient group consisting of 72 eyes of 36 patients who were diagnosed with unilateral optic neuritis, and an age-matched control group of 36 eyes of 18 healthy subjects. The patient group consisted of 25 multiple sclerosis patients and 11 recurrent isolated optic neuritis patients. The mean shear wave elastography values of the optic nerves and intraorbital fat tissue adjacent optic nerves were recorded using m/s and kPa as units. ROC curve analysis was performed, and the diagnostic accuracy of shear wave elastography values was determined. Results: The mean shear wave elastography values of the optic nerves with neuritis (2.49 ± 0.41 m/s and 17.56 ± 4.42 kPa) were significantly higher than the values of the contralateral normal optic nerves (1.71 ± 0.32 m/s and 9.02 ± 2.34 kPa) (p = 0.006 and p = 0.004, respectively) in the optic neuritis group. The mean shear wave elastography values of intraorbital fat tissue adjacent optic nerves with neuritis (1.87 ± 0.32 m/s and 9.65 ± 1.12 kPa) were significantly higher than the values of the contralateral normal side (1.47 ± 0.27 m/s and 6.78 ± 1.14 kPa) (p = 0.025 and p = 0.022, respectively) in the optic neuritis group. ROC curve analysis showed a high diagnostic accuracy for determining optic neuritis with shear wave elastography values of the optic nerves (AUC 0.955 [95% CI, 0.933–0.978] in m/s and AUC 0.967 [95% CI, 0.940–0.985] in kPa). Conclusions: Shear wave elastography may be an important alternative diagnostic tool in the diagnosis of optic neuritis.